Tacrolimus Pharmacokinetic and Pharmacogenomic Differences between Adults and Pediatric Solid Organ Transplant Recipients - Amy Lu; Jerry Altshuler; Kwaku Marfo (MDPI AG, 2010)
Tacrolimus is a calcineurin inhibitor immunosuppressant that has seen considerable use in both adult and pediatric solid organ transplant recipients. Though there is much pharmacokinetic data available for tacrolimus in the adult population, the literature available for children is limited. Furthermore, very little is known about the pharmacogenomic differences in the two patient groups. Based on what information is currently available, clinically significant differences may exist between the two populations in terms of absorption, distribution, metabolism and elimination. In addition, inherent physiological differences exist in the young child including: less effective plasma binding proteins, altered expression of intestinal P-glycoprotein, and increased expression of phase 1 metabolizing enzymes, therefore one would expect to see clinically significant differences when administering tacrolimus to a child. This paper examines available literature in an attempt to summarize the potential pharmacokinetic and pharmacogenomic variability that exists between the two populations.